(3HjGf eTcd GdBKGQs - (3GdWMGhj , CHh LYaQ,J (B321 (3g` s
(3ChdgG (B:s
(3jHJOF HHGH HjGf eTcd eG Qhi ai GdOjI s
(3BNQgG (B:s
(3hjfJgi HHGH HjGf eTcd eGQhi Yf QShd Gddg Udi Gddg Ydjg hSde ai fgjI Yf GdhbhY ai GdUdGI s
(3HBNQg agQS HGdCHhGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B107s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs